Plant Allometric Growth Enhanced by the Change in Soil Stoichiometric Characteristics With Depth in an Alpine Meadow Under Climate Warming - Xu, Manhou; Zhao, Zitong; Zhou, Huakun; Ma, Li; Liu, Xiaojiao (Frontiers in Plant Science, 2022)
The effects of global warming have caused the climate of the Qinghai-Tibetan Plateau (QTP) warm leading to changes in plant growth and soil nutrients in alpine meadows. However, few studies have addressed the effects of warming on plant allometric growth and soil stoichiometry in these meadows at a long-term scale. Therefore, the effects of soil stoichiometry on plant allometric growth remain unclear under long-term warming on alpine meadows. The present study adopted infrared radiators to conduct an 8-year warming experiment in a permafrost region on the QTP starting in 2010, and surveyed growth indices of the plant community during the growing season; soil organic carbon (C), total nitrogen (N), and total phosphorus (P) in an alpine meadow were measured. We initially learned that the aboveground part of alpine meadow vegetation in the warming treatment changed from an isometric to an allometric growth pattern while the allometric growth pattern of the belowground part was further strengthened. Second, the contents of soil C, N, and P decreased at the 0–20 cm depth and increased at the 20–30 cm depth in warming. The ratios of soil C:N, C:P, and N:P all showed increasing trends at different soil depths with artificial warming, and their amplitudes increased with soil depths. Warming promoted the migration of soil stoichiometric characteristics of C, N, and P to deep soil. Finally, correlations of plant growth with soil stoichiometric characteristics were weakened by warming, demonstrating that the downward migration of soil stoichiometric characteristics to deep soil in warming had effects on the growth of vegetation in the alpine meadow. It concludes that the change in soil stoichiometric characteristics with soil depths promotes plant allometric growth in the alpine meadow under climate warming.